1982
DOI: 10.1111/j.1476-5381.1982.tb09274.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vasoactive Intestinal Polypeptide and of Adenosine 5′‐triphosphate on the Isolated Anococcygeus Muscle of the Mouse

Abstract: Vasoactive intestinal polypeptide (VIP, 0.01–5 μm) produced dose‐related relaxations of the mouse anococcygeus muscle. Following incubation with indomethacin (2.8 μm 1 h) adenosine 5′‐triphosphate (ATP, 0.5–10 mm) produced dose‐related relaxations of the mouse anococcygeus. Haemolysed blood reduced inhibitory responses of the mouse anococcygeus to field stimulation but had no effect on relaxations to VIP or ATP. Apamin (0.5 μm) had no effect on the relaxation of mouse anococcygeus to field stimulation, VIP, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…In the present study, relaxations to nitrovasodilator drugs, like those to NANC stimulation, were blocked by NMH and potentiated by M&B 22948; this suggests that the NANC transmitter of the mouse anococcygeus resembles, in its mode of action, the nitrovasodilators and would be consistent with the possibility that the inhibitory factor, or a closely related substance, is the transmitter released by NANC nerves in the anococcygeus (Bowman & Gillespie, 1982). Whatever the transmitter, it seems clear that NANC transmission in the anococcygeus is the same as that in the retractor penis since NANC relaxations of both tissues are blocked by NMH (Bowman & Drummond, 1984;; this study) and haemolysed blood (Bowman & Gillespie, 1982;Gibson & Tucker, 1982;Gibson & Yu, 1983), are potentiated by M&B 22948 (Bowman & Drummond, 1984;this study), and are insensitive to block by apamin (Bowman & Gillespie, 1982;Gibson & Tucker, 1982).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In the present study, relaxations to nitrovasodilator drugs, like those to NANC stimulation, were blocked by NMH and potentiated by M&B 22948; this suggests that the NANC transmitter of the mouse anococcygeus resembles, in its mode of action, the nitrovasodilators and would be consistent with the possibility that the inhibitory factor, or a closely related substance, is the transmitter released by NANC nerves in the anococcygeus (Bowman & Gillespie, 1982). Whatever the transmitter, it seems clear that NANC transmission in the anococcygeus is the same as that in the retractor penis since NANC relaxations of both tissues are blocked by NMH (Bowman & Drummond, 1984;; this study) and haemolysed blood (Bowman & Gillespie, 1982;Gibson & Tucker, 1982;Gibson & Yu, 1983), are potentiated by M&B 22948 (Bowman & Drummond, 1984;this study), and are insensitive to block by apamin (Bowman & Gillespie, 1982;Gibson & Tucker, 1982).…”
Section: Resultsmentioning
confidence: 66%
“…VIP has been detected by immunocytochemistry and by radioimmunoassay in anococcygeus muscles from several species (Gibson & Tucker, 1982;Hunter et al, 1984;Larson et al, 1985). Since VIP was also a potent relaxant of these muscles it was considered as a possible candidate for the NANC transmitter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemoglobin reduced the responses to NO and the S-nitrosothiols, although it did not affect responses to IBMX. Previously, it has been shown that haemoglobin (in the form of haemolysed blood) inhibited NANC relaxations of the mouse anococcygeus without affecting those to VIP or ATP (Gibson & Tucker, 1982 (Hobbs et al, 1991). This and other observations (Gillespie & Sheng, 1989) have led to the proposal that NO may be released from the nerve attached to a carrier molecule, which protects it within the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%
“…During an investigation of the actions of putative inhibitory transmitters, excitation of these nerves by means of prolonged trains of field stimulation, caused a biphasic relaxation of the muscle (Gibson & Tucker, 1982). In this paper the results of some experiments carried out to characterize this phenomenon are detailed.…”
Section: Introductionmentioning
confidence: 99%